2009
DOI: 10.18256/2175-5027/psico-imed.v1n1p82-90
|View full text |Cite
|
Sign up to set email alerts
|

Triangulação de Informações: Bender, Anamnese e CBCL nas Dificuldades de Aprendizagem

Abstract: RESUMOEste artigo objetiva verificar a associação entre dificuldades escolares, obtidas por meio de entrevistas de anamnese, o item competência escolar do CBCL e os resultados do teste Bender. A amostra constitui-se de 1200 crianças, meninos e meninas, com idades entre cinco e 12 anos. Nas entrevistas de anamnese, o item mais freqüente foi a dificuldade de aprendizagem (16,6%). No CBCL, considerando a competência escolar, 13% das crianças demonstram dificuldades na área. Em se tratando do Teste Bender, o maior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…A study by Suehiro and dos Santos (2005) found performance in the Bender test worsened as the degree of learning difficulty of the participants increased. Other studies have found low visual-motor performance in adolescent school dropouts (Romi & Marom, 2005) and in children and adolescents with school competence problems (da Silva, Feil, de Souza, & Paniagua, 2009).…”
mentioning
confidence: 91%
“…A study by Suehiro and dos Santos (2005) found performance in the Bender test worsened as the degree of learning difficulty of the participants increased. Other studies have found low visual-motor performance in adolescent school dropouts (Romi & Marom, 2005) and in children and adolescents with school competence problems (da Silva, Feil, de Souza, & Paniagua, 2009).…”
mentioning
confidence: 91%